Comparison of fluticasone propionate and budesonide on COPD macrophage and neutrophil function - Belchamber,KBR; Thomas,C; Dunne,A; Barnes,P; Donnelly,L (International Journal of COPD, 2018)
Background: Inhaled corticosteroid (ICS) use is associated with increased rates of pneumonia in COPD patients. The underlying mechanism is unknown although recent data suggest that pneumonia is more frequent in patients treated with fluticasone propionate (FP) than budesonide. Macrophages and neutrophils from COPD patients are deficient in clearing bacteria and this might explain increased bacterial colonisation in COPD. ICS may further suppress this response; therefore, we examined the effect of FP and budesonide on phagocytosis of common respiratory pathogens by monocyte-derived macrophages (MDM) and neutrophils.Methods: MDM from COPD patients (n=20-24) were pre-incubated with FP or budesonide for 1 or 18 h after which phagocytosis of fluorescently labelled inert beads or heat-killed Haemophilus influenzae or Streptococcus pneumoniae were measured fluorimetrically after 1 or 4 h. Additionally, the following was measured: CXCL-8, IL-6 and TNFα concentrations in supernatants by ELISA, MDM scavenger receptor expression by flow cytometry, and the MDM ability to kill bacteria. Neutrophils from COPD patients (n=8) were pre-incubated with corticosteroids for 1 h, and phagocytosis of bacteria was measured by flow cytometry. Results: After 1 h pre-incubation, neither corticosteroid altered MDM phagocytosis of beads or H. influenzae; however, budesonide (10-7M) increased phagocytosis of S. pneumoniae by 23% (P<0.05). After 18 h pre-incubation, neither corticosteroid altered MDM phagocytosis of any prey, although phagocytosis of H. influenzae by budesonide was significantly greater compared to FP at 10-6 and 10-5M (P<0.05). The 1 h pre-incubation with either corticosteroid inhibited bacteria-induced CXCL-8 release (at 10-7 and 10-5M, P<0.05); however, this effect was lost at 18 h pre-incubation. There was no change in receptor expression, bacterial killing or neutrophil phagocytosis by either corticosteroid. Conclusions: These data suggest that dissolved FP an